Assessment Of Water Quality And Sustainability Of Situ Cilodong In Depok City, West Java Province - Sinta Kusumasari; Hariyadi Hariyadi; Moh. Yanuar Jarwadi Purwanto (Jurnal Ilmu Sosial Mamangan, 2024)
Situ Cilodong not only holds excellent tourism potential but also plays a vital role in the water management system of Cilodong District. It serves as a water storage container and a catchment area. According to a 2018 study conducted by the Depok City Government, Situ Cilodong serves various functions, including its potential as a tourist attraction, water resource provider, and flood control. However, these functions are at risk due to several existing problems, primarily pollution. Situ Cilodong's pollution results from various community activities in the catchment area, including the discharge of domestic liquid waste, industrial activities, fisheries, and water tourism. This research aims to assess the water quality of Situ Cilodong. The parameters being measured include temperature, Total Suspended Solids (TSS), turbidity, pH, Dissolved Oxygen (DO), Biological Oxygen Demand (BOD), nitrate, phosphate, Chemical Oxygen Demand (COD), and E. coli levels. The analysis will then be compared to the quality standards set by Government Regulation No. 22 of 2021. The water quality status is determined using the Pollution Index method. BOD parameters ranged from 3.4 – 9.6 mg/L, and E. coli ranged from 1600 MPN/100 ml. Situ Cilodong's Pollutant Index (IP) is 3.34. The results of the water quality analysis indicate that several parameters, including BOD and E. coli, exceed the quality standards. As a result, the water quality status of Situ Cilodong is classified as lightly polluted. So, efforts are needed to maintain and restore the sustainability of Situ Cilodong's water quality.